The açaí fruit (Euterpe oleracea) is renowned for its high content of bioactive compounds, particularly anthocyanins, but its low stability against pH, temperature, and light poses challenges for processing and preservation. This study evaluated the antioxidant capacity of anthocyanins extracted and microencapsulated by spray drying, using a combination of maltodextrin and gum arabic as encapsulating agents. During extraction, four treatments were analyzed by combining two pH levels (2 and 4) and two temperatures (45 °C and 65 °C). Treatment T1 (pH 2, 45 °C) showed the highest DPPH radical inhibition percentage (39.86%), while T4 (pH 4, 65 °C) showed the lowest (9.19%). The results indicate that less aggressive conditions favor the preservation of antioxidant activity. Furthermore, it was observed that the properties of the encapsulating agents significantly affect the thermal and structural stability of the microencapsulated product. This work highlights the importance of optimizing the extraction and subsequent microencapsulation conditions in order to preserve the bioactive compounds of açaí and its potential as a functional ingredient for the food industry. - Buendía Buendía, Cristopher Alejandro (2025)
The açaí fruit (Euterpe oleracea) is renowned for its high content of bioactive compounds, particularly anthocyanins, but its low stability against pH, temperature, and light poses challenges for processing and preservation. This study evaluated the antioxidant capacity of anthocyanins extracted and microencapsulated by spray drying, using a combination of maltodextrin and gum arabic as encapsulating agents. During extraction, four treatments were analyzed by combining two pH levels (2 and 4) and two temperatures (45 °C and 65 °C). Treatment T1 (pH 2, 45 °C) showed the highest DPPH radical inhibition percentage (39.86%), while T4 (pH 4, 65 °C) showed the lowest (9.19%). The results indicate that less aggressive conditions favor the preservation of antioxidant activity. Furthermore, it was observed that the properties of the encapsulating agents significantly affect the thermal and structural stability of the microencapsulated product. This work highlights the importance of optimizing the extraction and subsequent microencapsulation conditions in order to preserve the bioactive compounds of açaí and its potential as a functional ingredient for the food industry.